The millipede family Striariidae Bollman, 1893: III. Four new species of Striaria Bollman, 1888 (Diplopoda, Chordeumatida, Striariidae) from Idaho, USA - Shear, William A. (Zootaxa, 2021)
The millipede genus Striaria Bollman, 1888 heretofore had been thought to be confined to the Appalachian region of eastern North America, is replaced in western North America by species of the genus Amplaria Chamberlin, 1941. Collections from northern Idaho show that this is not the case, and that at least four species of Striaria occur in the west. These species are described herein as Striaria aculeata n. sp., S. bombillus n. sp., S. vagabundus n. sp. and S. orator n. sp.